Cholinergic Enhancement of Brain Activation in Mild Cognitive Impairment during Episodic Memory Encoding - Risacher, Shannon L.; Wang, Yang; Wishart, Heather A.; Rabin, Laura A.; Flashman, Laura A.; McDonald, Brenna C.; West, John D.; Santulli, Robert B.; Saykin, Andrew J. (Frontiers in Psychiatry, 2013)
Objective: To determine the physiological impact of treatment with donepezil (Aricept) on neural circuitry supporting episodic memory encoding in patients with amnestic mild cognitive impairment (MCI) using functional MRI (fMRI). Methods: 18 patients with MCI and 20 age-matched healthy controls (HC) were scanned twice while performing an event-related verbal episodic encoding task. MCI participants were scanned before treatment and after approximately 3 months on donepezil; HC were untreated but rescanned at the same interval. Voxel-level analyses assessed treatment effects in activation profile relative to retest changes in non-treated HC. Changes in task-related connectivity in medial temporal circuitry were also evaluated, as were associations between brain activation pattern, task-related functional connectivity, task performance, and clinical measures of cognition. Results: At baseline, the MCI group showed reduced activation during encoding relative to HC in the right medial temporal lobe (MTL; hippocampal/parahippocampal) and additional regions, as well as attenuated task-related deactivation, relative to rest, in a medial parietal lobe cluster. After treatment, the MCI group showed normalized MTL activation and improved parietal deactivation. These changes were associated with cognitive performance. After treatment, the MCI group also demonstrated increased task-related functional connectivity from the right MTL cluster seed region to a network of other sites including the basal nucleus/caudate and bilateral frontal lobes. Increased functional connectivity was associated with improved task performance. Conclusions: Pharmacologic enhancement of cholinergic function in amnestic MCI is associated with changes in brain activation pattern and functional connectivity during episodic memory processing which are in turn related to increased cognitive performance. fMRI is a promising biomarker for assessing treatment related changes in brain function.